Proximal renal tubular function in myelomatosis: observations in the fourth Medical Research Council trial. - Cooper, E H (1984)
Proximal renal tubular function was studied in 522 consecutive patients entered into the Medical Research Council's fourth myelomatosis trial. Assessment was made at presentation after a 48 h period of hydration but before administration of chemotherapy. The most common abnormalities in the urine other than light chain proteinuria were raised concentrations of the low molecular weight proteins alpha 1-microglobulin and alpha 1-acid glycoprotein. These were usually accompanied by increases in urinary beta-N-acetyl-D-glucosaminidase concentrations. The concentration of these substances in the urine directly correlated with urinary free light chain output. This tubular proteinuria was seen whether or not patients had impaired glomerular function, as assessed by a rise in serum creatinine concentration. Urinary concentrations of retinol binding protein, however, were generally increased only when serum creatinine concentrations were raised. This applied even when there were high concentrations of light chains, alpha 1-microglobulin, alpha 1-acid glycoprotein, and beta-N-acetyl-D-glucosaminidase in the urine. There is therefore a selective tubular proteinuria in myelomatosis which is seen in almost all patients with urinary light chain values greater than 1 u/l. This proteinuria is generally reversible, when light chains no longer appear in the urine. Patients whose serum creatinine was greater than 200 mumol/l, however, had increased urinary output of retinol binding protein in addition to increased excretion of alpha 1-microglobulin, alpha 1-acid glycoprotein, and beta-N-acetyl-D-glucosaminidase. Tubular proteinuria in many of these patients presenting in renal failure persisted even when light chain output was reduced after chemotherapy.